Analysis of Coral Fish Community Structure in Maitara Island (Sari Mauli Village and Teluk Ake), Tidore Islands City - Titaheluw, Syahnul S.; W. Laitupa, Ibnu; Bafagih, Aisyah; Andriani, Rovina (Agrikan Jurnal Agribisnis Perikanan, 2023)
This research aims to see the structure of reef fish community in Maitara Island (Ake Bay and Sari Mauli Village). This research was conducted in August 2023 using Visual Method Census. This study found that the number of fish censused at the research site was 497 fish with 50 species dominated by major fish as many as 32 species, target fish as many as 15 species and indicators as many as 3 species. Fluctuations in abundance, diversity and uniformity indices can be used as indicators of coral reef damage. The abundance of major fish in the study site was 0.58-0.60, diversity ranged from 0.29-0.32 and uniformity of major fish ranged from 0.32-0.43. Indicator group abundance ranged from 0.4-0.7, diversity ranged from 0-0.18 and uniformity ranged from 0-0.18. Indicator fish abundance ranged from 0.31-0.39, target fish diversity was 0.37 and uniformity ranged from 0.36-0.54..